Rights of People with Special Needs from a Legal Perspective - Noura Hamed Al-Harbi; Naseeba Jameel Al-Omari; Sheikha Abdulrahman Al-Yami (International Journal of Law Research and Studies, 2024)
Special needs are the diagnostic conditions of individuals who suffer from disabilities that limit their ability to perform normal activities. These individuals need special care to help them integrate into society. Those responsible for caring for people with special needs often need guidance from the competent authorities on how to deal with them. Special needs cases include those that recover quickly and also cases that are not expected to recover, such as: developmental delay, medical errors, psychological conditions, and congenital conditions. Therefore, people with special needs are individuals who have a disability or difficulty in movement, vision, hearing, speech, perception, mind, psychological disorders, autism, respiratory diseases, or other health conditions that affect their ability to interact with the world around them in a normal way. Individuals with special needs need special support and care from the community to enable them to live independently, fully engage in society, and obtain educational and employment opportunities equal to other individuals. The support available to individuals with special needs includes rehabilitation, training, treatment, employment, health care, dedicated public facilities, and other services that provide them with the necessary support to improve their quality of life. This research sheds light on the rights of this important group in society from a legal point of view and from the point of view of international agreements, with the aim of maximizing their positive participation in daily life, benefiting from them, and spreading the culture of effective communication with them.